Combating stigma and discrimination: the role oof religion in building inclusive communities responding to HIV & AIDS - Ecumenical Advocacy Alliance; World Conference of Religions for Peace; UNESCO (Norway Religions for Peace)
It is an outcome of a satellite session held during the XV International AIDS Conference in Bangkok, Thailand that brought together senior religions leaders from different faith traditions, as well as people living with HIV
Keywords: HIV/AIDS - Religious aspects; AIDS (Disease) -- Religious aspects -- Christianity